Pengaruh jumlah wisatawan terhadap jumlah objek halal tourism islamic pada sektor pariwisata di Kabupaten Pesawaran - Rohayatun, Riska; Ihsan, Budi; Riswan (Sekolah Tinggi Ilmu Ekonomi Syariah (STIES) ALIFA, 2023)
This research is included in the Quantitative Associative Research category, which aims to understand the relationship between two or more variables. This research was carried out using a field research approach, where data was obtained directly from the research location. The data used in this research includes tourism income, the number of halal Islamic tourism attractions, and the number of tourist visits from 2016 to 2022 in Pesawaran Regency. The research results show that there is a positive and significant relationship between the number of tourist visits (X1) and tourism sector income (Y) in Pesawaran Regency. This is proven by the t-statistic value of 4.082 with a probability of 0.002, which indicates that this variable has a significant influence on tourism sector income. Apart from that, there is also a positive and significant relationship between the number of halal tourism tourist attractions (X2) and tourism industry income (Y) in Pesawaran Regency. This can be seen from the t-statistic value of 2.519 with a probability of 0.029, which shows that this variable has a significant influence on tourism industry income.